Fast and efficient molecule delivery into Euglena gracilis mediated by cell‐penetrating peptide or dimethyl sulfoxide. Issue 4 (18th March 2023) - Gao, Pingwei; Sun, Chengfu
Abstract : This study describes the development of two methods for delivering exogenous materials into Euglena gracilis, a unicellular flagellate organism. We report that the use of Pep‐1, a short cell‐penetrating peptide (CPP), or dimethyl sulfoxide (DMSO) can mediate fast and efficient intracellular delivery of exogenous materials into E. gracilis, achieving cellular entry efficiency as high as 70–80%. However, compared with human cells, the penetration of this algal cell with CPP requires a much higher concentration of purified proteins. In addition, upon convenient treatment with DMSO, E. gracilis cells can efficiently adsorb exogenous proteins and DNA with 10% DMSO as the optimal concentration for Euglena cells. Our results provide more options for the E. gracilis transformation 'toolkit box' and will facilitate future molecular manipulations of this microalgal organism. Abstract : Methods for delivering exogenous molecules into Euglena gracilis are still limited. We provide here two simple methods with fast and efficient delivery performance for this alga. One method utilized the membrane entry ability of CPP and the other the membrane permeability of DMSO. Both can achieve over 70% delivery efficiency. Our methods promise to be beneficial for E. gracilis research.